Relationship between area-level socio-economic deprivation and autoantibody status in patients with rheumatoid arthritis: multicentre cross-sectional study. Issue 10 (22nd March 2012) - Mackie, Sarah L; Taylor, John C; Twigg, Sarah; Martin, Stephen G; Steer, Sophia; Worthington, Jane; Barton, Anne; Wilson, Anthony G; Hocking, Lynne; Young, Adam; Emery, Paul; Barrett, Jennifer H; et al.
Abstract : Objectives: The aims of this study were to assess the association between area-level socio-economic deprivation and the phenotype of rheumatoid arthritis (RA), defined by rheumatoid factor (RF) and anticitrullinated peptide antibody (AC PA) status, and to determine whether any observed association can be explained by smoking. Methods: The authors performed logistic regression analysis of 6298 patients with RA, defined by American College of Rheumatology classification criteria modified for genetic studies. Analysis was stratified by cohort/recruitment centre. Socio-economic deprivation was measured using the Townsend Index. Results: Deprivation predicted RF but not ACPA positivity, independent of smoking. The ORs for trend across tertiles, adjusted for smoking, gender, period of birth and cohort/recruitment centre, were 1.14 (95% CI 1.01 to 1.29) for RF and 1.01 (95% CI 0.87 to 1.16) for ACPA. Even after adjusting for deprivation, smoking was strongly associated with ACPA positivity (OR 1.38, 95% CI 1.22 to 1.55). There was no evidence of any effect modification by the RA risk alleles ( HLA-DRB1 shared epitope and PTPN22 rs2476601) that have previously been shown to modify the effect of smoking on ACPA and RF positivity. Conclusions: Among patients with RA, deprivation predicted RF positivity but not ACPA positivity. The effect of deprivation did not appear to be explained by smoking. Deprivation may be a marker for previously unrecognised, potentially modifiable environmental influences on the immunological phenotype of RA. Furthermore, given the known associations of RF positivity with prognosis and response to treatment in RA, these findings have potential implications for resource allocation and healthcare delivery.